2020
DOI: 10.1002/jcp.29520
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid protects ovariectomy‐induced bone loss in mice by inhibiting osteoclast differentiation and bone resorption

Abstract: Osteoporosis is a devastating disease that features reduced bone quantity and microstructure, which causes fragility fracture and increases mortality, especially in the aged population. Due to the long-term side-effects of current drugs for osteoporosis, it is of importance to find other safe and effective medications. Ellagic acid (EA) is a phenolic compound found in nut galls, plant extracts, and fruits, and exhibits antioxidant and antineoplastic effects. Here, we showed that EA attenuated the formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
(40 reference statements)
1
21
0
Order By: Relevance
“…Notably, EA downregulated the expression levels of TNF-α, ASC, p-p65, and other NLRP3 inflammasome-related proteins. These observations suggested that the regulatory effects of EA on hyperuricemia are related to its ability to inhibit the NLRP3 signaling pathway, similar to that reported for EA in protecting bone loss in mice through the attenuation of the NF-κB signaling pathway . Analysis of tissue morphology further showed that EA can protect against liver and renal damage, at least partially (Figure ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Notably, EA downregulated the expression levels of TNF-α, ASC, p-p65, and other NLRP3 inflammasome-related proteins. These observations suggested that the regulatory effects of EA on hyperuricemia are related to its ability to inhibit the NLRP3 signaling pathway, similar to that reported for EA in protecting bone loss in mice through the attenuation of the NF-κB signaling pathway . Analysis of tissue morphology further showed that EA can protect against liver and renal damage, at least partially (Figure ).…”
Section: Discussionsupporting
confidence: 71%
“…These observations suggested that the regulatory effects of EA on hyperuricemia are related to its ability to inhibit the NLRP3 signaling pathway, similar to that reported for EA in protecting bone loss in mice through the attenuation of the NF-κB signaling pathway. 40 Analysis of tissue morphology further showed that EA can protect against liver and renal damage, at least partially (Figure 6). Combined, these results demonstrated that the attenuating effects of EA on hyperuricemia-induced hepatorenal injury are likely mediated through directly inhibiting the NLRP3 pathway.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Furthermore, vanillic and syringic acids [119], resveratrol [115,120], catechins [121], caffeic acid [77], and chlorogenic acid [122] were found to decrease the number of RANKL-induced osteoclastogenesis by reducing RANKL/OPG ratio supported by the reduced ACP and TRAP activities and/or gene expression level in osteoporotic rat models and cells. Moreover, chlorogenic [123] and ellagic acids [124] stimulated osteoblast precursors proliferation and differentiation in ovariectomized animal models and suppressed RANKL-induced osteoclastogenesis through suppressing p38-MAPK signaling pathways. Furthermore, rutin [125] and P-coumaric acid [126] improved bone histomorphometry and biochemical markers of bone turnover associated with reduced osteoclastic activity, increased bone mass/body mass ratio and bone mineral mass/body mass ratio in ovariectomized mice.…”
Section: Discussionmentioning
confidence: 97%
“…As a result, there is still a need to discover new medications that are free of these adverse effects and could be applied long-term. Recently, natural plant extracts have been an attractive alternative drug for osteoporosis due to their low toxicity ( Zhan et al, 2019 ; Lin et al, 2020 ; Wang et al, 2021 ). Our study showed that mogrol, an aglycon of mogroside extracted from Siraitia grosvenorii (Swingle), has an inhibitory impact on osteoclast differentiation and function in vitro and protects against bone mass loss in postmenopausal mice.…”
Section: Discussionmentioning
confidence: 99%